Pengetahuan Perawat Terhadap Teknik Komunikasi SBAR di Satu Rumah Sakit di Indonesia Barat - Meilandy Watulangkow; Nadya Nalendra Sigar; Rumiris Manurung; Lia Kartika; Edson Kasenda (Poltekkes Kemenkes Bengkulu, 2020)
Patient safety is the main thing in client’s the treatment process. Nurses' knowledge or cognitive abilities are fundamental for nurses to carry out their duties and responsibilities. SBAR's effective communication technique consisting of Situation, Background, Assessment, Recommendation is known to minimize the possibility of errors in communication. This study aims to identify the description of nurses' knowledge of SBAR communication techniques. This study used a quantitative descriptive design, which was conducted from May to July 2019. The population in this study were all nurses who served in the inpatient room. The sampling technique used total sampling and involved 50 respondents. Knowledge is measured using an instrument about nurses' knowledge of effective SBAR communication techniques, valid with a Cronbach Alpha reliability of 0.851. Univariate data analysis showed that more than half of the respondents, 26 nurses (52%), had high knowledge of SBAR communication techniques. Collaborative efforts between educational institutions and hospitals on training and simulation of SBAR communication techniques are necessary to support client safety. Further research is needed to explore the relationship between characteristics, attitudes, and motivation with SBAR implementation.